Space Charge Behavior and Mechanism of Polyimide Under Pulse Voltage - Jianjian HOU; Chanjuan WANG; Haoxin GUO; Chen CHEN; Xuemin LIU; Dongxin HE (Zhongguo dianli)
The insulation of power electronic equipment is more likely to deteriorate and fail early because it is operated with high repetition rate and steep rise time pulse voltage for a long time. In order to explore the microscopic mechanism of insulation failure under pulse voltage, the space charge distribution before and after the pulse edge at the nanosecond level was studied and compared, and the influences of electric field strength and silicone oil on the charge vibration waveform at the pulse edge were explored. Based on an analysis of the spectrum of charge vibration waveform and voltage waveform and the charge accumulation characteristics at different pulse rise times, the charge vibration mechanism at the time of pulse voltage edge and the influence mechanism of charge behavior on insulation degradation under nanosecond pulse were expounded. It was found that the charge distribution characteristics before and after the rising edge and falling edge of the nanosecond pulse were different, and a special space charge migration behavior was found at the pulse edge; the electric field strength would affect the accumulation speed and amount of the heteropolar charge, thereby affecting the shape of charge vibration waveform; the application of silicone oil between the electrode and the sample would affect the polarity of the charge vibration waveform; the voltage component in the 5×106~1×107 Hz frequency band played a major role in the space charge vibration; the charge accumulation under the nanosecond pulse voltage caused serious electric field distortion.